Design and Implementation of a “Wireless-Hand” Mechatronic Prototype for the Control of a Robotic Hand - Peña Jaramillo, Eduardo Ivan; Alberti Villalobos, Pedro Enrique; Bustamante, S.; Maldonado Cardenas, Patricia Veronica; Barría, P. (My University, 2022)
The technological transfer between the areas of computer engineering and health have allowed collaborative work and effective support between both areas. This is how the development of robotics in the present can aid in repetitive activities or activities that present a lesser degree of direct intervention with the patient in certain therapies. This paper presents the design, creation, and programming of a "Wireless-Hand" mechatronic prototype that allows for remote control of a robotic hand. For this, a glove with flex sensors and micro-controlled circuits was designed, which connects wirelessly with the robotic hand, allowing communication and control over it. For the connection to be optimal in terms of data transfer and connectivity, three types of technologies are compared: Zigbee, Bluetooth, and WiFi.
Keywords: bluetooth; flex sensors; robotic hand; wifi; wireless transmission